(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
The dilute acid hydrolysis of corn stoverusing sulphuric acid at different concentrations (2.32-5.68% w/w), hydrolysis times (18-52 min) and hydrolysis temperatures (76-144°C) were studied. The total reducing sugar present in the hydrolysate was quantified using DNS Method. A ???????? five level Central Composite Design (CCD) was used to develop a statistical model for the optimization of process variables which are acid concentration, hydrolysis time and hydrolysis temperature. Response Surface Methodology (RSM) was employed for the optimization of the dilute acid hydrolysis conditions. The optimal hydrolysis conditions that resulted in the maximum total reducing sugar concentration were acid concentration of 4.99% (w/w), hydrolysis temperature of 90.09°C and hydrolysis time of 44.99 minutes. Under these conditions, the total reducing sugar concentration was obtained to be 20.9575 g/L. Quadratic model selected for the analysis was then validated.